Integrate prediction of machine learning for single ACoA rupture risk: a multicenter retrospective analysis - Li, Yang; Huan, Linchun; Lu, Wenpeng; Li, Jian; Wang, Hongping; Wang, Bangyue; Song, Yunfei; Peng, Chao; Wang, Jiyue; Yang, Xinyu; Hao, Jiheng (Frontiers in Neurology, 2023)
Background Statistically, Anterior communicating aneurysm (ACoA) accounts for 30 to 35% of intracranial aneurysms. ACoA, once ruptured, will have an acute onset and cause severe neurological dysfunction and even death. Therefore, clinical analysis of risk factors related to ACoA and the establishment of prediction model are the benefits to the primary prevention of ACoA. Methods Among 1,436 cases of single ACoA patients, we screened 1,325 valid cases, classified risk factors of 1,124 cases in the ruptured group and 201 cases in the unruptured group, and assessed the risk factors, respectively, and predicted the risk of single ACoA rupture by using the logistic regression and the machine learning. Results In the ruptured group (84.8%) of 1,124 cases and the unruptured group (15.2%) of 201 cases, the multivariable logistic regression (MLR) model shows hemorrhagic stroke history (OR 95%CI, p:0.233 (0.120–0.454),<0.001) and the age stratification of 60–69 years (OR 95%CI, p:0.425 (0.271–0.668),<0.001) has a significant statistic difference. In the RandomForest (RF) model, hemorrhagic stroke history and age are the best predictive factors. Conclusion We combined the analysis of MLR, RF, and PCA models to conclude that hemorrhagic stroke history and gender affect single ACoA rupture. The RF model with web dynamic nomogram, allows for real-time personalized analysis based on different patients’ conditions, which is a tremendous advantage for the primary prevention of single ACoA rupture. Clinical trial registration https://www.chictr.org.cn/showproj.html?proj=178501.